INTERSECTION OF RACE AND SEXUALITY IN THE QUIET VIOLENCE OF DREAMS - Sourav Upadhyaya; Saurav Mitra; Dwitun Basumatary; Sarangadhar Baral (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
K. Sello Duiker’s novel The Quiet Violence of Dreams (2001) is an important intervention in the area of sexuality studies. The book is a twenty-first century critique of the idea of compulsive heterosexuality. The text looks at the binaries of heterosexuality and homosexuality manifested in linguistic construction and powered through a network of institutions. In Duiker, the ‘spectral’ presence of homosexuality is compounded by the presence of the great divide that race brings within leading to what Stockton calls, “intrusion of narratives on narratives” (Stockton 117). This paper proposes to interrogate Duiker’s critique of compulsive heterosexuality. Central to the analysis is the exploration of the interconnectedness between race and sexuality. Intersection of sexuality and race leads to new dynamics, of oppression and resistance. This is intricately connected to notions of identity and power. This paper will also interrogate Duiker’s exploration of Un-African character of homosexuality and how he reimagines African sexuality anew. The intertwining of these aspects magnifies the complexities of existence, exemplified through Tshepo's experiences as a black gay man. The text's portrayal of Tshepo's journey becomes emblematic of the broader quest for authenticity, unearthing the intricate layers that define the multidimensional experiences of those at the crossroads of race and sexuality.